Tomas Chamorro-Premuzic: the human-plus-AI evolution and its risks - Leavy, Brian (Strategy & leadership, 2023)
Purpose This is a thought-leader interview with psychologist Tomas Chamorro-Premuzic on his insights into the implications for our humanity of the AI age. Design/methodology/approach A thought-leader interview Findings The interview highlights six maladaptive human tendencies that are at risk of being amplified in the age of AI and what we can do to mitigate them Originality/value The interview examines the latest thinking on the topic.